Citizen H2D3 - Empowering citizens to eat well and live well - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2020)
Citizen H2D3 is a scalable, realtime data collection system, gathering information on household dietary diversity from volunteers